Effects of a Universal Adhesive System and the Snow-Plow Technique on Microleakage of Class II Composite Restorations in Primary Molars - Mahshid Gifani; Mahsa Talafi Noghani; Alireza Sarraf Shirazi; Alireza Boruziniat (Frontiers in Dentistry)
Objectives: This study evaluated the effects of using a universal adhesive and application of a flowable composite by the snow-plow technique on microleakage of Class II composite restorations in primary molars.